PHYLOGENETIC GROUPING OF THE PATHOGENIC E. COLI ISOLATED FROM COMMERCIAL BROILER CHICKEN IN PAKISTAN - F. Akhtar; M. Rabbani; K. Muhammad; M. Younus; A. A. Sheikh; R. Akhtar; J. Muhammad; A. Rasool (Journal of Animal and Plant Sciences, 2016)
E. coli isolates can be classified into four different phylogenetic groups on the basis of chuA, yjaA and TspE4.C2 biomarkers via multiplex PCR. Current study investigated the presence of various phylogenetic groups in clinical samples of collibacillosis from commercial broiler chicken in Pakistan. A total of 84 E. coli isolates out of 200 swab sample (n = 25 cloacal; n = 27 fibrinous layer of peri-hepatitis of clinically infected broiler chicken; and n = 32 cloacal swabs from clinically healthy chicken) were recovered. Out of 25 pathogenic E. coli isolates from cloacal swabs, 12%, 4%, 72% and 0% isolates belonged to group A, B1, D and B2, respectively. Out of 27 pathogenic E. coli isolates from swab of fibrinous layer,18.5%, 29.6%, 44.4% and 0% isolates belonged to group A, B2, D and B1, respectively. While out of 32 non pathogenic E. coli isolates from healthy birds, 21.8%, 9.3%, 46.8% and 18.7% isolates belonged to group A, B2, D, and B1, respectively. There were 06 uncategorized E. coli isolates, which amplified both yjaA and TspE4.C2 biomarkers. This study helped to categorize the E. coli isolates into intestinal and extra intestinal origin on the basis of phylogenetic grouping.
Keywords: Collibacillosis; Fibrinous peri-hepatitis; Multiplex PCR